A Case Study Of Factors Influencing Speech Delay In Toddlers - Fitriazahra, Mawar; Siswanti, Dian Novita; Jafar, Eka Sufartianingsih (Pasundan Social Science Development, 2024)
The problem of speech delay in children is quite a serious problem because it is one of the most common causes of developmental disorders found in male toddlers. Children can be said to have speech delays when the level of speech development is below the level of speech development quality of children of the same age which can be seen from the accuracy of word use. This study focuses on what are the dominant factors in cases of speech delay in toddlers. This study uses a qualitative method with a case study approach. The unit of analysis is speech delay. The subjects in this study were five male toddlers and one female toddler who experienced speech delays. The informants in this study numbered four people consisting of five parents and one sister of the subject. Data collection techniques used interviews, observations, and supporting documentation to strengthen the truth of the data taken. The results of the data analysis showed that the cause of speech delay in children was due to the duration of gadget use, as well as the communication style between parents and children. The implications of this study can help in early identification of speech delays in toddlers, so that intervention can be carried out earlier.